Isolation and Identification of Pathogenic Fungi from Air Conditioners in Tutorial Rooms of the Faculty of Medicine, Universitas Padjadjaran - Gowre Govindasamy; Usep Abdullah Husin; Yoni Fuadah Syukriani; Sunarjati Sudigdoadi; Yanti Mulyana (Althea Medical Journal, 2014)
Background: Awareness about health problems caused by air conditioner is very important. Thus, it is crucial to have knowledge about proper maintenance of air conditioner. At the Faculty of Medicine, Universitas Padjadjaran, air conditioners are used in every tutorial rooms. This study was performed to provide adequate information on the fungi, such as Aspergillus, Penicillium and Mucor, found in air conditioners.Methods: A descriptive laboratory study was used to identify the presence and the type of pathogenic fungi from air conditioners in tutorial rooms. Thirty-four samples were collected from the air outlet grille of the air conditioners and cultured on Sabouraud agar at 27°C for 2 weeks. Fungi presence were then identified microscopicallyResults: The results showed that the majority of air conditioners in tutorial rooms of the Faculty of Medicine, University Padjadjaran contained many types of fungus that grew in Sabouraud agar. From 34 samples, thirty two samples were positive and 2 samples were negative. Various fungus have been identified, those were Penicillium (37.5%), Aspergillus (25%), Mucor (2.5%) and unidentified (35%)Conclusions : The majority of air conditioners in tutorial rooms of the Faculty of Medicine, University Padjadjaran contained many types of opportunistic fungus. [AMJ.2014;1(1):21–4]Keywords : Air conditioner, Aspergillus, fungi, Mucor, Penicillium Isolasi dan Identifikasi Jamur Patogen dari Pendingin Udara di Kamar Tutorial dari Fakultas Kedokteran, Universitas PadjadjaranLatar Belakang: Kesadaran tentang masalah kesehatan yang disebabkan oleh pendingin udara sangat penting. Dengan demikian , sangat penting untuk memiliki pengetahuan tentang perawatan yang tepat dari pendingin udara. Di Fakultas Kedokteran, Universitas Padjadjaran, pendingin udara digunakan di setiap kamar tutorial . Penelitian ini dilakukan untuk memberikan informasi yang memadai tentang jamur, seperti Aspergillus, Penicillium dan Mucor, yang ditemukan di pendingin udara. Metode: Sebuah studi laboratorium deskriptif digunakan untuk mengevaluasi keberadaan dan jenis jamur patogen dari pendingin udara di kamar tutorial. Tiga puluh empat sampel dikumpulkan dari kisi-kisi pendingin udara dan dikultur pada Sabouraud agar pada 27 °C selama 2 minggu. Pertumbuhan jamur kemudian diidentifikasi secara mikroskopis.Hasil: Hasil penelitian menunjukkan bahwa pada sebagian besar pendingin udara di ruang tutorial Fakultas Kedokteran Universitas Padjajdjaran terdapat banyak jamur yang dapat tumbuh di Sabaroaud agar, 32 hasil positif dan 2 hasil negatif untuk pertumbuhan jamur . Jamur yang tumbuh adalah Penicillium (37,5%, Aspergillus (25%), Mucor (2,5%) dan tidak teridentifikasi (35%).Simpulan : Sebagian besar pendingin udara di ruang tutorial Fakultas Kedokteran Universitas Padjadjaran Jatinangor menunjukkan adanya pertumbuhan jamur oportunistikKata kunci : Aspergillus, jamur , Mucor , Penicillium, pendingin udara DOI: 10.15850/amj.v1n1.292